2020
DOI: 10.1515/cog-2018-0020
|View full text |Cite
|
Sign up to set email alerts
|

Causality, subjectivity and mental spaces: Insights from on-line discourse processing

Abstract: Research has shown that it requires less time to process information that is part of an objective causal relation describing states of affairs in the world (She was out of breath because she was running), than information that is part of a subjective relation (She must have been in a hurry because she was running) expressing a claim or conclusion and a supporting argument. Representing subjectivity seems to require extra cognitive operations.In Mental Spaces Theory (MST; Fauconnier, Gilles. 1994. Mental spaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Additionally, fictionality revealed in [6,27] is not found as potent in the attested stimuli. Perspective construal appears highly predictive in cross-modal switches in Text AOIs (here displayed in Author / Speaker), which correlates with the results reported in Kleijn et al [21]. Importantly, R 2 with FFD and AFD in Text AOIs is higher in cross-modal switches, which means that several event construal operations in Text AOIs in bimodal systems produce steadier gaze effects.…”
Section: Gaze Behavior As Affected By Event Construal In Text Aoissupporting
confidence: 88%
See 2 more Smart Citations
“…Additionally, fictionality revealed in [6,27] is not found as potent in the attested stimuli. Perspective construal appears highly predictive in cross-modal switches in Text AOIs (here displayed in Author / Speaker), which correlates with the results reported in Kleijn et al [21]. Importantly, R 2 with FFD and AFD in Text AOIs is higher in cross-modal switches, which means that several event construal operations in Text AOIs in bimodal systems produce steadier gaze effects.…”
Section: Gaze Behavior As Affected By Event Construal In Text Aoissupporting
confidence: 88%
“…For instance, EMF was tested in eye tracking research in [10] where it allowed to determine the effects of space construal and agentivity in textual descriptions presented together with the images. In [21], the eye tracking procedure was applied to explore the effects of subjectivity in event construal as a component of EMF. It is noticeable that referent construal and event frame construal (event characteristics such as its dynamicity) effects are most tested in eye tracking psychological studies which are not attributed to EMF.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that processing subjective causal relations like She worked hard, because she passed the oral English test is more difficult than processing objective relations like She passed the oral English test, because she worked hard ( Traxler et al, 1997 ; Canestrelli et al, 2013 ; Kleijn et al, 2021 ), since the former involves a subjective (but implicit) speaker who expresses opinions, arguments, or attitudes but the latter is describing real-world cause-consequence facts. The present study extends the literature by suggesting a perspective alignment between the comprehender and the speaker during the online processing of (inter)subjective discourse relations.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, what is described in (2b) concerns the speaker’s reasoning such that the observation that she passed the oral English test (p) is an argument for the claim that she worked hard (q) . Relations like (2a) are considered as an objective relation and those like (2b) subjective, respectively ( Sanders and Spooren, 2015 ; Kleijn et al, 2021 ; see also “content domain” and “epistemic domain”, respectively, by Sweetser, 1990 ).…”
Section: Introductionmentioning
confidence: 99%